Content and composition of pentose in buckwheat flour (Fagopyrum esculentum Moench) - Zlata LUTHAR (Acta Agriculturae Slovenica)
The total pentose quantity in buckwheat flour of cvs. Siva, Darja, Petra and Bednja 4n was determined using the volumetric bromide-bromate method. The Molisch test was used to determine the presence of carbohydrates in hydrolysates (72% H2SO4) and, in the same samples,  high-performance  liquid  chromatography  (HPLC) - based  on  ion-exchange chromatography and after-column reaction derivation with copper 2,2’-bicinchoninate and detected by using a UV-VIS spectrophotometer - was used to determine monosaccharides glucose (hexose) and xylose (pentose). We established that the only pentose present in buckwheat flour is xylose, whose content in different analysed cultivars ranged from 5.44 to 6.51%.